PENGARUH IKLAN DAN HARGA TERHADAP VOLUME PENJUALAN PADA UKM CATERING A3 DI KP PALASARI KABUPATEN SUKABUM: Manajemen pemasaran - Neneng Yanti Andriani & ALDA SINABELLA (P3M STIE PASIM Sukabumi, 2020)
This study examines the influence of advertising and prices on sales volume at A3 Catering SMEs in KP Palasari Sukabumi Regency, the method used, the research conducted using the survey method, the type of technique used is saturated sampling or census sampling, namely the technique of determining the sample if all members population is used as a sample. The hypothesis proposed is that there is an effect of advertising and price simultaneously on sales volume. In the ANOVA table, it can be seen that the calculated F value is 30.072 when viewed from the Sig value. 0.000 < 0.05 then the decision is that there is a simultaneous influence of Advertising and Price on Sales Volume at A3 Catering SMEs in KP Palasari Sukabumi Regency. the correlation value r = 0.749 which means it is between the value of 0.600-0.799 which means it has a strong relationship, the nature of the relationship is positive, which means that if advertising and price on sales volume are good or increase then sales volume will also increase. the value of the coefficient of determination Kd = R2x100% = (0.749x0.749) = 0.561x100 = 56.1% so the KD value is the same as the value of R Square X1 and X2 contributes to Sales Volume by 56.1% the remaining 43.9% is influenced by other variables other than Advertising and Price which were not examined by the researcher. Y regression equation Based on the results of the output in the Unstandardized Coefficients table that is interpreted is Y = 1.220 + 0.528 + 0.775 Stating that if the presence of advertisements and prices increases, the Sales Volume Value will also increase by 0.775 points;’